Local anisotropy of muon flux during Forbush decreases from URAGAN data. (July 2015) - Barbashina, N; Ampilogov, N; Astapov, I; Borog, V; Dmitrieva, A; Kovylyaeva, A; Kokoulin, R; Kompaniets, K; Mannocchi, G; Mishutina, Yu; Petrukhin, A; Saavedra, O; et al.
Abstract: The approach to the analysis of spatial-angular characteristics of the muon flux variations at different phases of Forbush decrease development according to the muon snapshots (muongraphies) obtained using muon hodoscope URAGAN, as well as the analysis results are presented.